1992
DOI: 10.1148/radiology.182.3.1535886
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic shock in children: CT findings associated with hemodynamic instability.

Abstract: Twenty-seven of 1,018 children evaluated with contrast material-enhanced computed tomography (CT) after blunt trauma demonstrated a characteristic hypoperfusion complex. This complex was usually seen in young children (median age, 2 years). CT findings in all 27 patients included a dilated, fluid-filled bowel and abnormally intense enhancement of the bowel wall, mesentery, kidneys, aorta, and inferior vena cava. Twenty-four percent of all children with a Trauma Score of 10 or less and 20% with a Glasgow Coma S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 0 publications
1
64
0
3
Order By: Relevance
“…The results of this experimental study have been substantiated in a clinical report on patients with a reduced CO due to hypovolemic shock and systemic hypotension, where CT showed an unusually dense opacification of arteries, bowel walls, and kidneys [15]. Fleischmann et al [24] reported in patients with abdominal aortic aneurysms a correlation between the enhancement in the abdominal aorta and the contrast agent transit time, indicating an increase in vessel enhancement with lower CO.…”
Section: Hemodynamic Parameters and Coronary Opacificationsupporting
confidence: 55%
See 1 more Smart Citation
“…The results of this experimental study have been substantiated in a clinical report on patients with a reduced CO due to hypovolemic shock and systemic hypotension, where CT showed an unusually dense opacification of arteries, bowel walls, and kidneys [15]. Fleischmann et al [24] reported in patients with abdominal aortic aneurysms a correlation between the enhancement in the abdominal aorta and the contrast agent transit time, indicating an increase in vessel enhancement with lower CO.…”
Section: Hemodynamic Parameters and Coronary Opacificationsupporting
confidence: 55%
“…An additional important factor affecting the timing of contrast medium enhancement is cardiac output (CO) [14]. It has been clinically observed that reduced CO results in delayed and increased vascular enhancement [15]. Despite the importance of cardiac function for vessel opacification, to our knowledge, no study has investigated the influence of cardiac hemodynamic parameters on coronary artery attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…body mass index (BMI), body surface area (BSA)) [9][10][11] or by contrast bolus dilution depending on cardiac output (CO) [12][13][14]. Coronary calcifications are known to influence image quality by their blooming and beam-hardening artifacts [1,4,7].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) is the most common imaging examination performed in patients with acute abdominal pain, and imaging signs of acute adrenal ischemia, usually consisting of an enlarged hypodense adrenal without significant enhancement after IV contrast material injection, have to be considered in order to promptly diagnose this condition [5][6][7][8][9][10][11]. In case of suspected acute adrenal ischemia, the distinction between non-traumatic adrenal hemorrhage and hypovolemic shock needs to be made in order to preserve adrenal function by implementing rapid and correct treatment, although shock can also be a cause of adrenal ischemia and infarction if not promptly treated [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%